Utilization of "Wordwall" Media in Increasing Digital Literacy in Third-grade Students at Pajang III State Elementary School - Hanifah, Dini; Prayitno, Harun Joko; Adhantoro, Muhammad Syahriandi; Purnomo, Eko; Pradana, Fajar Gemilang; Kurniaji, Ganno Tribuana (International Conference on Education for All, 2024)
This Classroom Action Research (PTK) is based on the results of research regarding efforts to improve literacy learning achievement in digital literacy of third-grade through the learning medium "Wordwall" at Pajang III State Elementary School. The aim of this research is to improve students digital literacy outcomes through the use of "Wordwall" media. Classroom Action Research (PTK) was carried out in two cycles. The subjects of this research were 24 third-grade students at Pajang III State Elementary School. The instruments used in this research include classroom observations, questionnaires, and digital literacy skills tests using the learning medium "Wordwall." This can be seen in the significant increase in the percentage of students who use "Wordwall" media for learning. In the first cycle, the average percentage of student learning outcomes was 41%, but increased to 83% in the second cycle. From the analysis of research data, it can be concluded that there has been a significant increase in student learning outcomes in digital literacy using "Wordwall" media.